Effect of processing techniques and conditions on properties of composite polymeric film - Ahed Zabadi; Salam Sa'ad; Muna Sleem; We'am Dweikat (My University, 2012)
The main objective of this project is to study the effect of processing techniques and conditions on the properties of polyethylene composite film such as mechanical properties like strength, toughness, ductility, elongation and modulus. Two methods were used to prepare the polyethylene films. The first one is the melting method using process molding technique under variable conditions (e.g. temperature of the mold and cooling rate). The second one is the cold method by dissolving the polymer  in xylene (solvent), followed by casting the polymer solution onto a mold and either immerse it into a nonsolvent (i.e. water or alcohol) or directly expose it to the air. The second part of this thesis was to make a composite polymer films through blending the polymer with different food waste like pistachio shell, olive kernel, avocado seed and almond shell with different concentrations. It was found that the films cooled by quenching in ice (i.e. highest cooling rate) showed the lowest elastic modulus, maximum yield and ultimate strength in comparison with the samples formed by cooling in ambient air or by water jacket.  In addition increasing the pressing temperature increases the elastic modulus of the films; samples cooled from the pressing temperature (i.e 200 C) showed higher elasticity modulus than those prepared by pressing at 180 C. The difference in the mechanical properties of the films as a result of the different cooling conditions and press-molding temperature was ascribed to the crystallization rate of the films which is dependent on the cooling rate and time. Besides, the preparation method of the films strongly affects their MFI solution-casting samples showed higher MFI values than those prepared with thermal press-molding. The results showed also that the composites prepared by blending the polymer with pistachio shell (with 5% concentration) showed better mechanical properties than other food additives especially for elastic modulus which was higher than that of neat LLPDEL films.